P039 Interventions used to increase sleep duration in young people: A systematic review. (7th October 2021) - Gadam, S; Pattinson, C; Soleimanloo, S; Rossa, K; Moore, J; Begum, T; Srinivasan, A; Smith, S
Abstract: Introduction: Habitual short sleep duration affects a substantial proportion of young people, which is problematic due to its association with various adverse consequences. The aim of this systematic review was to identify the effectiveness of current interventions to increase sleep duration in healthy young people (14–25 years). Methods: A systematic literature search, following PRISMA guidelines was conducted across multiple databases including PubMed, Ovid MEDLINE, CENTRAL, Embase, CINAHL (via EBSCOhost), PsycINFO, Scopus, Web of Science, ProQuest Dissertations and Theses, and Trove. Eligible studies were required to report sleep duration before and after exposure to the intervention, published from 2005 onwards, and participants 14–25 years of age. The Newcastle-Ottawa scale and Cochrane Risk of Bias were used to evaluate quality of studies. Results: 2695 citation were screened, and 29 studies met the eligibility criteria for this review. The included studies implemented differing methodologies, including behavioural (48.3%), educational (24.1%), and combination (24.1%) of behavioural, educational and other methods, such as mindfulness, light therapy, and naturalistic observation (3.4%). Initial findings indicate that educational interventions on their own are not effective at increasing sleep duration as behavioural or combination of both. Discussion: These results indicate that behavioural interventions which prescribe new sleep schedules show positive treatment effects on sleep duration. Hence, provide promise for mitigating sleep difficulties and improving health in young people aged 14–25 years.